The Roles of Post-translational Modifications on α-Synuclein in the Pathogenesis of Parkinson’s Diseases - Zhang, Jiaming; Li, Xiaoping; Li, Jia-Da (Frontiers in Neuroscience, 2019)
Parkinson’s disease is the second most common neurodegenerative disorder. Although the pathogenesis of Parkinson’s disease is not entirely clear, the aberrant aggregation of α-synuclein has long been considered as an important risk factor. Elucidating the mechanisms that influence the aggregation of α-synuclein is essential for developing effective diagnostic, preventative and therapeutic strategy to treat this devastating disease. The aggregation of α-synuclein is influenced by several post-translational modifications. Here, we summarized the major post-translational modifications (Phosphorylation, Ubiquitination, Truncation, Nitration, O-GlcNAcylation) of α-synuclein and the effect of these modifications on α-synuclein aggregation, which may provide potential targets for future therapeutics.